2021
DOI: 10.3390/su132011173
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Physical, Chemical and Nano-Microstructure Characteristics of Asphalt Mixed with Recycled Eggshell Waste

Abstract: Green economy is a major them of sustainable development. The application of biological waste in engineering is conducive to green development. This study reveals the effect of recycled eggshell waste on the physical and chemical properties as well as nano-microstructure characteristics of asphalt. The hardness, thermal stability and ductility of asphalt were explored by the penetration, softening point and ductility tests. The distribution and relative content of protons in asphalt were revealed by nuclear ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Some scholars have found that the eggshell powder has a rough, porous and loose structure, which improves the strange hardness and thermal stability. Its interaction with asphalt is a physical miscibility process [ 18 ]. When eggshell powder is mixed into asphalt, it makes asphalt hard and increases moisture susceptibility [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have found that the eggshell powder has a rough, porous and loose structure, which improves the strange hardness and thermal stability. Its interaction with asphalt is a physical miscibility process [ 18 ]. When eggshell powder is mixed into asphalt, it makes asphalt hard and increases moisture susceptibility [ 19 ].…”
Section: Introductionmentioning
confidence: 99%